ANALYSIS OF THE FUNCTIONAL STATE OF MAIN TRANSPORT SYSTEMS OF BLOOD PLASMA OF PATIENTS WITH ACUTE LEUKEMIA AND CHRONIC MYELOGENOUS LEUKEMIA AFTER TRANSPLANTATION THE HEMATOPOIETIC STEM CELLS BY FLUORESCENT PROBES METHOD - E. V. Korolik; A. A. Ivanov; N. I. Insarova; O. M. Morozova; N. F. Milanovich; A. L. Uss (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Using the fluorescent probes method the conformational changes in albumin have been found in case of chemotherapy high dozes applied for treatment of patients with acute myeloid leukemia, as well as the inflammatory process has been decreased after the transplantation of hematopoietic stem cells.